Debating education for nation building in Malaysia: National school persistence or vernacular school resistance? - Sivapalan Selvadurai; Ong, Puay Liu; Marsitah Mohd Radzi; Ong, Puay Hoon; Ong, Puay Tee; Badariah Saibeh (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
School and education system may be a critical and strategic platform for nation-building. At the same time, the politicization of the education system as well as the interdependent nature of schools and external forces may contribute to the destabilization of the role of school in nation building. In Malaysia, the issue of mono-lingualism as a medium of instruction in schools has been a contested one with efforts of accommodating bilingualism and multilingualism continue to be attempted with no solutions in sight. The persistence of vernacular schools has generated both intense debates and resistance. This article examines the reasons for the resistance to, and persistence of vernacular schools. The data were drawn from three main sources, namely interviews with heads and/or representatives of 12 schools (mostly national schools and Chinese schools) from four states namely Selangor, Kelantan, Sarawak and Sabah as part of a wider project on social cohesion study as well as newspapers and web sources. The resistance to vernacular schools was premised on the affirmation that national schools rest on the idea of inculcating and sustaining national identity as well as facilitating cross-cultural experience and communication while eliminating the more segregating and divisive forces in vernacular schools. By contrast, the persistence of vernacular schools pertains to the idea of sustaining minority cultural identity, countering the lack of national schools’ sense of accommodation and questionable quality of education, and refuting the perception of vernacular schools as structural cause of disunity. Besides these negotiation difficulties of cultural identities in the school system, wider power politics and market politics interplay in influencing the resistance and persistence of vernacular schools.